Ijmâ’ Ulama Dan Relevansinya Dari Masa Ke Masa - Imam Sucipto; Oyo Sunaryo Mukhlas (ISLAMICA, 2016)
Ijma’ is one of the three sources of Islamic law after the Qur'an and hadith. Ijma’ is theconsensus of the mujtahids in establishing a law that has not been written in the Qur'an and hadith, so the need for an excavation of a certain legal provisions through deliberation and consensus. In its development consensus is not only about the laws of Personality but rather is extended to matters of a general nature concerning the interests of Muslims.